The Relationship between Facts and Norms in Judicial Legal Reasoning: An Analysis of the Ratio Decidendi in Court Decisions - Doni Sabdan Tanjung; Rahmayanti, Rahmayanti; Donly Calner Aruan; Faisal Lutfi (PT. Sinergi Legal Publisher, 2026)
Court decisions are the result of a judge's legal reasoning process that reconciles legal facts with legal norms through juridical argumentation. The essence of this process is reflected in the ratio decidendi, namely the legal reasoning that forms the basis for determining the verdict. This article aims to analyze how the relationship between facts and norms is constructed in the judge's legal reasoning through the construction of the ratio decidendi in court decisions. This study uses a normative legal research method with a conceptual approach and a case approach. The conceptual approach is used to examine the theory of legal reasoning, legal facts, legal norms, and the concept of ratio decidendi, while the case approach is used to examine the judge's legal considerations in court decisions. The results show that the relationship between facts and norms in court decisions is not mechanical, but rather is constructed through a process of fact selection, norm interpretation, and rational legal argumentation. The ratio decidendi serves as a meeting point between facts and norms and as an indicator of the quality of the judge's legal reasoning. The clear, coherent, and argumentative construction of the ratio decidendi reflects the responsible use of the judge's discretion and contributes to the realization of legal certainty and substantive justice in judicial practice.